If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(x + 2) = 2x + -6 Reorder the terms: 5 + -1(2 + x) = 2x + -6 5 + (2 * -1 + x * -1) = 2x + -6 5 + (-2 + -1x) = 2x + -6 Combine like terms: 5 + -2 = 3 3 + -1x = 2x + -6 Reorder the terms: 3 + -1x = -6 + 2x Solving 3 + -1x = -6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + -1x + -2x = -6 + 2x + -2x Combine like terms: -1x + -2x = -3x 3 + -3x = -6 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + -3x = -6 + 0 3 + -3x = -6 Add '-3' to each side of the equation. 3 + -3 + -3x = -6 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = -6 + -3 -3x = -6 + -3 Combine like terms: -6 + -3 = -9 -3x = -9 Divide each side by '-3'. x = 3 Simplifying x = 3
| 3x-9=2x+4 | | 6+3j=21 | | 5q-14=8q | | 6X+15=5X+20 | | x/4+9=14 | | 8-6n=-70 | | 2+12x=-18+7x | | -4/9w=-16 | | 5x-6y=-18 | | -29=-6x+1 | | 12h^2-31h+20=0 | | 88-24=34/5(h-6) | | -7(4x-2)+9=-28x+23 | | 6+x-2 | | X=-17 | | p-24=34/5(20-6) | | x-7y+7z=-27 | | 2x+16=29 | | p-24=34/5(18-6) | | 5=9-x^2 | | 6+4x=4+6x | | 1/2x+3=8x+19/8 | | 1/2x+3 | | 26x+38=22x+55 | | -7m-3=-31 | | 1/4x+2=8x+11/8 | | 2x=4x+34 | | 3-(-3)= | | 3x-2x-16=0 | | 8T+12=19 | | 20+12x=7x | | 5v^2+v-42 |